Molecular Identification of Tomato Yellow Leaf Curl Virus and its Whitefly Vector (Bemisiatabaci) - Aqeel N. Al-Abedy (Journal of Global Pharma Technology, 2018)
This study was conducted in the Plant Virology Laboratory of Plant Protection Department at College of Agriculture-Karbala University to isolate and identify three viral isolates, which isolated from diseased tomato (Solanumlycopersicum L.) plants grown in farms of the desert region in Najaf, Karbala, and AL-Muthanna provinces in Iraq. In addition, this study also aimed at identifying the biotype of whitefly (B. tabaci) in 10 different locations in Najaf, Babylon, and Karbala. Identification of TYLCV and white flies was done on the basis of the PCR technique and determining the nucleotide sequences of the PCR-amplified products.   Results, obtained from the PCR amplification and analysis of nucleotide sequences of the amplified products of the viral isolatesusing BLAST (Basic Local Alignment Search Tool), showed that the three isolates belong to Tomato yellow leaf curl virus (TYLCV). Comparison of the nucleotide sequences generated from the identified TYLCV isolates with the nucleotide sequences deposited at the National Center for Biotechnology Information (NCBl) revealed that the identified TYLCV isolates (A1MA, A2MA, and A3MA) were not previously recorded at NCBI. Therefore; these identified sequences have been deposited and recorded in GenBank database (NCBI) under the accession numbers: KT961703, KU145132, and KT961704, respectively. From the analysis of the mitochondrial cytochrome oxidize I (mtCO I) sequence of B. tabaci using BLAST program, results indicated that the biotype B whitefly is the only biotype prevalent in sampling region and none of the collected whitefly samples contains either the Q biotype or any other whitefly biotype.